Polar Chromosomes—Challenges of a Risky Path - Kruno Vukušić; Iva M. Tolić (Cells, 2022)
The process of chromosome congression and alignment is at the core of mitotic fidelity. In this review, we discuss distinct spatial routes that the chromosomes take to align during prometaphase, which are characterized by distinct biomolecular requirements. Peripheral polar chromosomes are an intriguing case as their alignment depends on the activity of kinetochore motors, polar ejection forces, and a transition from lateral to end-on attachments to microtubules, all of which can result in the delayed alignment of these chromosomes. Due to their undesirable position close to and often behind the spindle pole, these chromosomes may be particularly prone to the formation of erroneous kinetochore-microtubule interactions, such as merotelic attachments. To prevent such errors, the cell employs intricate mechanisms to preposition the spindle poles with respect to chromosomes, ensure the formation of end-on attachments in restricted spindle regions, repair faulty attachments by error correction mechanisms, and delay segregation by the spindle assembly checkpoint. Despite this protective machinery, there are several ways in which polar chromosomes can fail in alignment, mis-segregate, and lead to aneuploidy. In agreement with this, polar chromosomes are present in certain tumors and may even be involved in the process of tumorigenesis.